Ефективність застосування відеореклами для популяризації готельно-відпочинкових комплексів - Чура, Юлія; Думанський, Нестор (Видавництво Львівської політехніки, 2015)
This article is talking about efficiency of video advertising for popularization of hotel services. Posted advantages of video advertising and usage statistics of different types of advertising aimed at creating an image of hotels.
Keywords: реклама; відеопрезентація; ефективність; відеохостинг; готельні послуги